Letras por um fio: a tradução intersemiótica do conto a moça tecelã, de Marina Colasanti nos bordados de Matizes Dumont - Bouty, Alessandra Marinho (2018)
Man tell stories ever since he is aware of his presence in the world, and through narrative he understands himself as part of a greater whole. Above all things, narrating is an exposition and exchange of experiences through drawings, gestures, orality and writing that are manifested in colors, sounds, images, sensations and senses involving all together: narrated object, narrator and its receiver. When a narrative migrates from its original language to a different one, occurs a process of translation between signs, rich in interpretations and meanings. This is the case, for example, when a literary narrative is taken to embroidery, where lines that fill the space of the fabric gain meaning as important as the letters and words that make up for a tale. Taking as foundation the intersemiotic translation of the tale A Moça Tecelã by Marina Colasanti, embroidered by Matizes Dumont group to ilustrations in the 2004 publication of Editora Global, this dissertation is divided in two parts. In O Direito, it brings to reflection what is seen in the embroidery of Matizes Group, its materiality and the meanings of the images, as a haptic body for the words written by Colasanti and as a visual narrative permeated by mythical references. In O Avesso, it’s drawn an overview of the relations that ground the object, intrinsic to the evolution and the transformations of the embroidery as a feminine practice, as culture and as a result of the creative gesture of the hands.